TANGGUNG JAWAB PELAKU USAHA TERHADAP PENJUALAN PAKAIAN BEKAS IMPOR YANG MERUGIKAN KONSUMEN DI PASAR KODOK TABANAN - A.A. Sagung N.Indradewi; Ni Putu Sri Windayati (Kerta Dyatmika, 2019)
Pasar Kodok Tabanan is well-known as a market that sells the largest imported used clothing in Bali, imported used clothing has less quality so that it can couse losses to consumers. Law number 7 of 2014 concerning Trade in article 47 paragraph 1 states that each importer has to import goods in a new condition and based on Law number 8 of 1999 concerning Consumer Protection in article 8 paragraph 2 states that business actors are prohibited to trade damaged, defective or used and contaminated goods without providing complete and correct information on the intended goods. The focuses of this research are how the responsibilities of imported used clothing business actors harm the consumer in Pasar Kodok Tabanan and how the role of government overcomes the practice of buying and selling imported used clothing that can harm the consumers. The research method in writing this essay was: the types of research qualified as empirical legal research. The source of legal material is primary data that directly obtained from the sources and secondary data as primary legal material or data sourced from regulations and books. Material collection techniques were collected by observing, interviewing, and documenting. Data was processed by analytical descriptive. The results of the research showed that those used clothing importers have a tendency to not be responsible for compensation that should be a consumer right based on the article 19 of the Consumer and used clothing business actors can also hold accountable for various aspect of civil, legal, and administrative law. Protection and the Government is responsible for the guidance and supervision of consumer protection which guarantees the consumers rights and business actors as well as the implementation of the obligations of consumers and business actors. Industry and trade service Tabanan regency provides appeals to traders to think about business activities that can harm consumers and provide education to make easier in buying products. Keywords: imported used clothing, consumer loss, business actors’ responsibilities